Penerapan Literasi Sejarah Dalam Pembelajaran Sejarah Pada Masa Pembelajaran Jarak Jauh di SMA - Ayuningtias Rahman; Kurniawati; Murni Winarsih (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2021)
Abstract: This study aims to determine the application of historical literacy in learning the history of the online distance learning at SMA Negeri 30 Jakarta. In this study using a qualitative method with a case study approach The data collection techniques used were: (1) in-depth open-ended interviews; (2) observation and (3) document analysis, with the key informants of history teachers and class X IPS students. The results of the research conducted show that the application of historical literacy in SMA Negeri 30 Jakarta has been well implemented by teachers, especially during the online distance learning Even though the teacher's conceptual understanding of the concept of historical literacy is less detailed and the level of student literacy is still in the low category. From the observations, the teacher has been able to apply historical literacy according to the dimensions of historical literacy by Maposa and Wasserman (2009). The main challenge experienced by teachers in the application of historical literacy is that the level of student literacy is still low so that it affects the application of historical literacy in history learning. Keywords : Historical Literacy, Distance Learning, History Learning Abstract : Artikel ini bertujuan untuk mengetahui penerapan literasi sejarah dalam pembelajaran sejarah masa Pembelajaran Jarak Jauh (PJJ) dalam jaringan di SMA Negeri 30 Jakarta. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data yang digunakan yaitu: (1) in-depth open-ended interviews; (2) observasi dan (3) analisis dokumen, dengan informan kunci guru sejarah dan siswa Kelas X IPS. Hasil dari penulisan yang dilakukan menunjukan bahwa penerapan literasi sejarah di SMA Negeri 30 Jakarta telah diterapkan dengan baik oleh guru terlebih pada masa pembelajaran jarak jauh (PJJ). Walaupun pemahaman konseptual guru mengenai konsep literasi sejarah yang kurang mendetail serta tingkat literasi siswa yang masih dalam kategori rendah. Dari hasil pengamatan, guru telah mampu menerapkan literasi sejarah sesuai dimensi literasi sejarah Maposa dan Wasserman (2009). Tantangan utama yang dialami guru dalam penerapan literasi sejarah adalah tingkat literasi siswa masih rendah sehingga berpengaruh pada penerapan literasi sejarah dalam pembelajaran sejarah. Kata kunci : Literasi Sejarah, Pembelajaran Jarak Jauh (PJJ), Pembelajaran Sejarah